2020
DOI: 10.1039/d0ra00313a
|View full text |Cite
|
Sign up to set email alerts
|

Spectral evidence for generic charge → acceptor interactions in carbamates and esters

Abstract: NMR, FT-IR spectral correlations of the R–O–CO groups in carbamates and esters of homologous alcohols (R) reveal R-group-dependent negative charge stabilization at the carbonyl oxygen and its donation to generic acceptors at Cα of even alkyl R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Schädel et al. reported carbamate rotational barriers of Δ G =15.2 kcal/mol and Δ G= 15.1 kcal/mol for the symmetric bis(2‐(2‐vinylsulfonyl)ethoxy)ethyl tert ‐butyl carbamate and the asymmetric methyl(2‐(2‐vinylsulfonyl)ethoxy)ethyl tert ‐butyl carbamate, respectively [12] . Wiest et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Schädel et al. reported carbamate rotational barriers of Δ G =15.2 kcal/mol and Δ G= 15.1 kcal/mol for the symmetric bis(2‐(2‐vinylsulfonyl)ethoxy)ethyl tert ‐butyl carbamate and the asymmetric methyl(2‐(2‐vinylsulfonyl)ethoxy)ethyl tert ‐butyl carbamate, respectively [12] . Wiest et al.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis using the modified Eyring equation [35,36] resulted in the rotational energy barrier of A exp (II) = 15.93 � 0.59 kcal/mol, in close agreement with the computed estimate of A rot (VII). Rotational barriers were also determined experimentally for similar N,N-dialkyl O-alkyl carba- [12] Wiest et al showed that N-alkyl-Nphenyl alkyl carbamates may feature even lower rotational barriers such as ΔG = 12.3 kcal/mol for methyl(phenyl) tert-butyl carbamate. [9] The CN rotation of ureas R 4 R 3 NÀ COÀ NR 1 R 2 have been shown to be similar to carbamates but proceed with smaller rotational barriers than carbamates.…”
Section: Chemphyschemmentioning
confidence: 99%
See 2 more Smart Citations
“…Such compaction between H α s is characteristic of residue pairs interacting between strands in antiparallel β‐sheets [31,32] . This HαA ⋅⋅⋅HαG ROE crosspeak intensity is only slightly reduced (43 %) in presence of a weaker H‐bond acceptor carbonyl (of Boc carbamate) [33] in 2 (Figures 3 and S4). The ROE (33 %) is retained in the N‐methylated model 3 (Figures 3 and S5) in which the alternate 12‐membered H‐bonded ring structure is not possible (Figure 3).…”
Section: Figurementioning
confidence: 97%